100 things you should know about Science - Parker, Steve; Miles Kelly Publishing; Riley, Peter (Miles Kelly Publishing Limited: Essex, 2004)
This volume, one in a series of books, opens up the world of science to children. 100 numbered facts will challenge children, and act as an incentive as they make their way through the book. Projects to make and do are included.
Keywords: Science